Analisis Tingkat Kepuasan Pengguna Aplikasi Employee Self Service di PT Indofood CBP Sukses Makmur Tbk Menggunakan Metode End User Computing Satisfaction - Yoga Wahyu Pratama; Fransiska Prihatini; Orissa Octaria; Ahmad Farisi; Mardiani Mardiani (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
The use of technology in data management has become the key to improving the efficiency and effectiveness of company performance. PT Indofood CBP Sukses Makmur Tbk has implemented a computerized employee attendance system through the Employee Self Service (ESS) application. However, so far there has been no evaluation regarding the level of user satisfaction with the application. This study aims to measure ESS user satisfaction to provide input in future application development. The method used is End User Computing Satisfaction (EUCS) which includes five variables: Content, Accuracy, Format, Ease of Use, and Timeliness. Data was obtained through the distribution of questionnaires and analyzed using the SPSS application. The results of the t-test showed that the Format variable had the most significant influence (t = 4.281), while the other variable showed an insignificant influence individually. However, through the F test, an F value was obtained of 3.791 with a significance of 0.003, which shows that simultaneously all EUCS variables have a significant effect on user satisfaction. These results are expected to be the basis for companies to improve the performance of ESS applications and support the overall work efficiency of employees.